The Decrease of Leaf Dark Respiration during Water Stress Is Related to Leaf Non-Structural Carbohydrate Pool in Vitis vinifera L. - Sergio Tombesi; Tommaso Frioni; Francesca Grisafi; Paolo Sabbatini; Stefano Poni; Alberto Palliotti (Plants, 2021)
Dark respiration (Rd) is a fundamental plant process used to gain biomass and maintain plant physiological activity. It accounts for the metabolization of a large share of the carbon fixed by photosynthesis. However, Rd during conditions of severe plant water stress is still poorly understood. The decrease in leaf transpiration increases temperature, one of the most important drivers of leaf Rd. On the other hand, water stress decreases the pool of leaf carbohydrates, which are the most important substrate for respiration. The aim of the present work was to determine the impact of water shortage on leaf Rd in grapevine and understand the driving factors in modulating leaf Rd response under plant water stress conditions. Water stressed vines had lower Rd as the water shortage severity increased. Rd was correlated with leaf temperature in well-watered vines. Instead, in water stressed vines, Rd correlated with leaf soluble sugars. The decrease of leaf Rd in water stressed vines was due to the decrease of leaf non-structural carbohydrate that, under water stress conditions, exerted a limiting effect on Rd.